Second Generation Biobutanol: An Update - Dian Burhani; Eka Triwahyuni; Ruby Setiawan (Reaktor, 2019)
Butanol, a rising star in biofuel, can be produced by two approaches, petrochemically and biologically. Currently, the most promising route for butanol production is by fermentation using Clostridium species through an anaerobic condition. However, similar to other biofuels, feedstock has greatly influenced the production of biobutanol and the search for inexpensive and abundant raw material is an absolute requirement for a cost-effective process. Second-generation biobutanol which is produced from lignocellulosic biomass of agricultural and forestry waste not only meets the requirement but also alleviates competition with food crops and thereby solves the problems of food scarcity from the first generation biobutanol. This paper delivered the latest and update information regarding biobutanol production specifically second-generation biobutanol in terms of production method, recovery, purification, status, and technoeconomic.  Keyword: biobutanol, lignocellulose, purification, recovery, technoeconomic